Desain Destilator Dua Atap Miring dengan Memanfaatkan Panas Gas Buang Mesin Diesel - Baride, La; Maturbongs, Yustinus Edward K. (Politeknik Negeri Ujung Pandang, 2018)
The general objective of this research is to generate destilator prototype that utilize heat exhaust gas from engine fishing boats, while specific objective of this research is to generate usefull technology, to generate fresh water for the needs on fishing boats, to increase the productivity of fisherman through the efficiency of sailling time while processing sea water to be fresh water on fishing boat. This research uses experimental method. Destilator was designed as destillation tool of sea water with utilizing heat from exhaust gases of diesel machine. The result of the research for three hours with the volume of distilled water 25 liters were obtained; on machine circle 2200 rpm fresh water generated is 4465 ml with the temperature of sea water 89 oc effectiveness of destilator 66.06 % with heat loses 0.1891kj/s; on machine circle 2000 rpm of fresh water generated is 3700 ml with the temperature of sea water 87 oc, effectiveness of destilator 65.79 % with heat loses 0.068 kj/s; on machine circle 1800 rpm of fresh water generated is 2940 ml with the temperature of sea water 83 oc effectiveness of of destilator 64.36 % with heat loses 0.0313kj/s.